Erroneous Belief that Digestive Stability Predicts Allergenicity May Lead to Greater Risk for Novel Food Proteins - Herman, Rod A.; Roper, Jason M. (Frontiers in Bioengineering and Biotechnology, 2021)
There continues to be an erroneous belief that allergens (especially food allergens) are more resistant to gastrointestinal digestion than non-allergens. Government regulations based on this erroneous belief may result in technology developers altering the amino acid sequences of digestively stable native proteins to create digestively unstable modified versions for expression in genetically engineered crops. However, an investigation where a known stable allergen was modified to make it more digestible eliminated the protein’s ability to tolerize against allergy in a mouse model, which is consistent with the dual allergen exposure hypothesis. Thus, the false belief that digestive stability increases the allergenic risk of novel food proteins (e.g., such as expressed in genetically engineered crops) could, in some cases, lead to introduction of digestively unstable modified protein versions with greater sensitization risk. However, it is noteworthy that developers have historically been very effective at preventing allergens from being introduced into crops based on the other components of the weight-of-evidence assessment of allergenic risk such that no newly expressed protein in any commercialized genetically engineered crop has ever been documented to cause allergy in anyone.